PSXI-11 Effects of pasture grazing on growth performance, herbage intake and blood composition of Hanwoo heifers during the growing stage. (7th December 2018) - Jung, J; Choi, K; Kim, H
Abstract: This study investigated the effect of pasture grazing on growth performance, forage intake, and blood characteristics in 12 six-month-old Hanwoo (native Korean cattle) steers. Steers were randomly assigned to two groups that were either pasture grazed (PG) or fed through a barn feeding system (BFS) with rice straw and concentrates (1.5% body weight (BW)). The former grazed on a 7 ha grassland from April to November by rotational grazing method, supplemented with concentrates (1.2% BW). From April to October 2017, the dry matter yields of the grass was 7565 kg ha -1 and the total amount of forage intake in the grassland was 4982 kg ha -1 . Initial BWs of BFS and PG were 231 ± 50 kg and 245 ± 54 kg, respectively. Average daily gains of both groups did not differ significantly, at 0.82 kg and 0.84 kg, respectively. Blood characteristics, such as glucose, gamma glutamyl transpeptidase (G-GTP), total cholesterol (T-CHO), and non-esterified fatty acid (NEFA) were investigated to test the effects on health and energy metabolism. Glucose levels increased in BFS (79.00 to 96.67 mg/dL) and decreased in PG (97.50 to 85.33 mg/dL), suggesting that BFS increases energy metabolism. G-GTP was lower in PG (7.67 IU/L) than in BFS (19.83 IU/L), suggesting that grazing is less damaging to the liver. T-CHO, an index of fat metabolism and liver function, was lower in PG (124.83 md/dL) than BFS (156.83 mg/dL). NEFA, a stress related index, was lower in PG (36 uEq/L) than in BFS (140.83 uEq/L). These results indicate that grazing is less stressful compared to BFS.